Could the COVID-19 Positive Asymptomatic Tobacco Smoker be a Silent Superspeader? - Muscat Baron, Yves (Acta Biomedica Atenei Parmensis, 2021)
There appears to be a connection between COVID-19 infection and an airborne microscopic pollutant called particulate matter which has been suggested to act as vector for viral transmission. The highest human exposure to particulate matter occurs during smoking and to a lesser extent applies to 2nd hand smoking. This article offers a hypothetical proposition that particulate matter derived from tobacco smoking may act as COVID-19’s vector for infection transmission. With a background smoking Chinese male population of more than 66% and more than 70% of Chinese nonsmokers exposed to 2nd hand smoke the potential of exhaled smoke acting as a viral vector is significant. If this hypothesis is proven, measures such as face protection to reduce coronavirus-laden particulate matter transmission, measures of social distancing and legislation to protect nonsmokers from contracting the infection through 2nd hand smoking should be implemented.